EVALUATION OF ANTIHYPERLIPIDEMIC ACTIVITY OF LEAVES OF ACHYRANTHES ASPERA Linn USING HYPERLIPIDEMIC RATS - Cn, Sarvesh; Fernandes, Jennifer (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Plants have been one of the important sources of medicines since the beginning of human civilization. Achyranthes aspera Linn. belonging to family Amaranthaceae, commonly found in India. The plant is used as antiarthritic, purgative, diuretic, antimalarial, etc. Methods: The antihyperlipidemic activity of alcoholic and aqueous extracts of leaves of A. aspera was evaluated using triton-induced hyperlipidemia model in albino Wistar rats. The acute toxicity study confirmed that both the extracts were found to be safe at 5000 mg/kg b.w. in female albino Wistar rats. In this model, eight groups (six animals per group) of animals were used. Group I and II were considered as saline and hyperlipidemic controls, respectively, and other groups received their respective agents (alcoholic or aqueous extract/atorvastatin/ayurvedic preparation) and all the groups received triton WR1339 (200 mg/kg b.w. i.v.) except saline control group. Serum cholesterol and triglycerides (TGs) level are estimated for the evaluation of antihyperlipidemic effects of extracts. Results: The ethanolic extract has shown a significant reduction in serum cholesterol and TGs level indicating antihyperlipidemic potentials in the plant while aqueous extract has not shown any beneficial effect. Conclusion: In this triton-induced hyperlipidemia model, serum and TG levels were analyzed ethanolic extract was shown antihyperlipidemic activity. Further clinical studies are compulsory to confirm the findings. Keywords: Achyranthes aspera, High-density lipoprotein, Low-density lipoprotein, Triglyceride, Total cholesterol, Triton, Antihyperlipidemic.